2019
DOI: 10.29252/jmp.2.70.212
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Investigation of Ethnobotany of Some Medicinal Plants in Razavi Khorasan Province

Abstract: Introduction: Ethnobutany, as a part of every region's national capital, contains local beliefs and knowledge about plants and their characteristics being the result of centuries of trial and error in the natural environment. Though, it is unwritten and exposed to degeneration. Purpose: The purpose of this study was to acquire and document the culture of traditional use of Zebarkhan rangeland medicinal plants from Neyshabur in Razavi Khorasan province. Method: In this study, the traditional knowledge of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The rich flora can be related to the diverse topo-climatic zones in the region from warm low elevation plains in the south to snow caped mountains and cold high elevation plains in the north, providing habitat for different plant species. Lamiaceae and Asteraceae are two main medicinal families in Iran 35 , 36 . The dominance of these two families can be attributed to their widespread distribution in the area and their diverse traditional medicinal uses for the pastorals.…”
Section: Discussionmentioning
confidence: 99%
“…The rich flora can be related to the diverse topo-climatic zones in the region from warm low elevation plains in the south to snow caped mountains and cold high elevation plains in the north, providing habitat for different plant species. Lamiaceae and Asteraceae are two main medicinal families in Iran 35 , 36 . The dominance of these two families can be attributed to their widespread distribution in the area and their diverse traditional medicinal uses for the pastorals.…”
Section: Discussionmentioning
confidence: 99%
“…[13] in the results of their research included the collection and identification of selected traditional uses of plants in Babol, and reported that the largest consumption of medicinal plants used by local communities belonged to Lamiaceae, Compositae and Legominaceaee. The studies of [14] in Ardestan located in Isfahan province, [15] in Zabarkhan rangelands in Neishabour, [16] in Shazand, Markazi province, [17] in Behbahan, Khuzestan province, [18] in forest-rangelands of Tuskistan, Golestan province and [19] in Azad Jammu and Kashmir, Pakistan, also, supported this statement. According to the research of [14] 120 species belong to 41 families, [15] 70 species belong to 29 families, [16] 56 species belong to 23 families, [20] 61 plant species belong to 29 families and [21] 119 species belong to 43 families.…”
Section: Discussionmentioning
confidence: 76%
“…Phlomis cansellata is used to relieve dandruff and head lice. Decoction of Achillea millefolium acts as an anti-nausea and helps treat diabetes, supported by [15], [22] and [23].…”
Section: Discussionmentioning
confidence: 99%
“…ex Fisch. for treating flatulence and disinfecting the environment (Alimirzaei et al, 2017;Hosseini et al, 2019Hosseini et al, , 2020. Additionally, Foeniculum vulgare Miller is known for regulating female hormones and increasing milk supply, Rosmarinus officinalis L. has blood thinning properties, and Lavandula angustifolia Mill.…”
Section: Medicinal Usementioning
confidence: 99%